Decreased Body Mass Index (BMI) in COVID-19 Patients with Anosmia Symptoms - Ristanto, Riki; Murtadho, Maulana Arif (Babali Publisher, 2024)
Introduction: COVID-19 is a respiratory infection caused by the SARS-CoV-19 virus and impacts the appearance of anosmia symptoms. Anosmia impacts reducing appetite, so it impacts fulfilling the nutritional needs of COVID-19 patients. This study aims to determine the effect of anosmia on the nutritional status of COVID-19 patients. Methods: This study is an observational study with a retrospective cohort design. The samples of this study were 48 health record data of COVID-19 patients who experienced anosmia in Karangploso View Housing, Malang Regency, from July to December 2021, selected according to the inclusion and exclusion criteria. The independent variable in this study is the incidence of anosmia felt by residents. The dependent variable is residents' Body Mass Index (BMI) before and after recovering from COVID-19 infection. This study was conducted from July 15 to August 11, 2023. Research data analysis using the SPSS version 22 program using the paired T-test and Wilcoxon test with α = 5%. Results: The paired T-test results on the weight variable showed a significant difference in the patient's weight between before and after COVID-19 illness with symptoms of anosmia (p-value = 0.000). The results of the Wilcoxon Test on the BMI variable showed a significant difference in the nutritional status (BMI) of respondents between before and after COVID-19 illness with symptoms of anosmia (p-value = 0.000). Conclusion: The condition of anosmia alters a person's food preferences, resulting in the perception of certain foods as less pleasant, bland, and unappealing. This condition results in loss of appetite, inadequate nutrient intake, and potential malnutrition. Self-efforts to prevent malnutrition due to anosmia in COVID-19 patients: using aromatic herbs and spices, eating small and frequent meals, modifying food texture and color seasoning, and consulting a dietician to develop a balanced and nutrient-rich meal plan.